Influence of Ozonated Water on Solid Ehrlich Tumor Induced in MICE: Clinical and Anatomopathological Study - de Araújo, Diego Pereira; de Paula Nascente, Eduardo; de Curcio, Juliana Santana; Arnhold, Emmanuel; de Paula Silveira Lacerda, Elisângela; Matos, Moema Pacheco Chediak; Fonseca-Alves, Carlos Eduardo [UNESP]; de Moura, Veridiana Maria Brianezi Dignani (Taylor & Francis, 2025)
This study was based on clinical and anatomopathological evaluations of the solid Ehrlich tumor (SET) experimentally induced in mice, treated with different ozonized water protocols. A total of 198 animals were used, divided into four groups: two treated with ozonized water at concentrations of 5 ppm-5 mg/L (G1/N = 60) and 8 ppm-8 mg/L (G2/N = 60); a vehicle control group with physiological sodium chloride solution (G3/n = 60); and a negative control group (NCG/N = 18). Groups were further subdivided by administration route (intratumoral and peritumoral), number of ozonized water applications (one or two), and observation periods after applications (24 hours, five days, and 30 days). No differences were observed between groups in terms of behavioral changes, tumor volume, or survival rates. However, an increase in necrotic area was noted in all groups treated with ozonized water at 24 hours and in some groups at 30 days. Mitosis counts were lower in groups treated with a higher ozone concentration at both 24 hours and 30 days. It is concluded that treatment with ozonized water did not induce adverse clinical effects, promoting increased necrosis and reduced mitosis counts, suggesting a direct antineoplastic effect of medical ozone applied to this tumor type.